MEMPREDIKSI NILAI PERUSAHAAN: APAKAH COMPANY GROWTH, TINGKAT PERTUMBUHAN LABA, DAN GOOD CORPORATE GOVERNANCE PENTING? - Widyaningsih, Sri; Sari, Shinta Permata (Balance : Jurnal Akuntansi dan Bisnis, 2024)
Prediction of firm value is done to evaluate the effectiveness of the company's strategy and prospects in maintaining its products or services, so as to attract investor interest. This study seeks to analyze the impact of company expansion, profit growth rate, and corporate governance on firm value. The subjects of this study are listed companies in the IDX-IC Energy Sector on the IDX in the 2019-2022 time span. This study applied purposive sampling method for data collection and utilized multiple linear regression analysis for data analysis. This study concludes that firm growth and corporate governance, indicated by the size of the board of commissioners and audit committee, have an effect on firm value, while earnings growth rate has no impact on firm value.